Learnings from an Ongoing Deployment of an IVR-based Platform for Voter Awareness - Mothilal, Ramaravind Kommiya; Mehta, Devansh; Sharma, Alok; Thies, Bill; Sharma, Amit (2019)
Spreading awareness among voters is a critical first step towards ensuring democratic participation. We report results from an ongoing deployment in India where we use an Interactive Voice Response (IVR) system to raise awareness about voting. People can call in to the number and answer a few questions on voting. They receive a mobile airtime top-up if they answer correctly, and an explanation of the correct answer if they do not. The system also serves as a survey instrument and we use it to collect data on the percentage of people who have their voter ID cards that enable them to vote. Extending past work on IVR-based mass awareness, we employ a different way of presenting content—a quiz instead of a tutorial—and of incentivizing usage—no monetary incentive for referrals except for specified referrers. In 24 days of deployment, over 1900 people have called the system, out of which 1245 answered all questions correctly in their first attempt, and 234 answered correctly after learning from their initial incorrect answers.